Abuse potential and adverse cognitive effects of mitragynine (kratom). (28th September 2014) - Yusoff, Nurul H. M.; Suhaimi, Farah W.; Vadivelu, Raja K.; Hassan, Zurina; Rümler, Anne; Rotter, Andrea; Amato, Davide; Dringenberg, Hans C.; Mansor, Sharif M.; Navaratnam, Visweswaran; Müller, Christian P.
Abstract: Mitragynine is the major psychoactive alkaloid of the plant kratom/ketum. Kratom is widely used in Southeast Asia as a recreational drug, and increasingly appears as a pure compound or a component of 'herbal high' preparations in the Western world. While mitragynine/kratom may have analgesic, muscle relaxant and anti‐inflammatory effects, its addictive properties and effects on cognitive performance are unknown. We isolated mitragynine from the plant and performed a thorough investigation of its behavioural effects in rats and mice. Here we describe an addictive profile and cognitive impairments of acute and chronic mitragynine administration, which closely resembles that of morphine. Acute mitragynine has complex effects on locomotor activity. Repeated administration induces locomotor sensitization, anxiolysis and conditioned place preference, enhances expression of dopamine transporter‐ and dopamine receptor‐regulating factor mRNA in the mesencephalon. While there was no increase in spontaneous locomotor activity during withdrawal, animals showed hypersensitivity towards small challenging doses for up to 14 days. Severe somatic withdrawal signs developed after 12 hours, and increased level of anxiety became evident after 24 hours of withdrawal. Acute mitragynine independently impaired passive avoidance learning, memory consolidation and retrieval, possibly mediated by a disruption of cortical oscillatory activity, including the suppression of low‐frequency rhythms (delta and theta) in the electrocorticogram. Chronic mitragynine administration led to impaired passive avoidance and object recognition learning. Altogether, these findings provide evidence for an addiction potential with cognitive impairments for mitragynine, which suggest its classification as a harmful drug.